DESIGN OF SALES PERFORMANCE DASHBOARD BASED ON SALES FUNNEL & SALES FORCE AUTOMATION THEORIES: A CASE OF AN INDONESIAN ISLAMIC BANK - Gani, Mardhiah; Hanafi, Rosmalina; Amar, Kifayah (International Journal of Islamic Banking and Finance Research, 2021)
One of the bank management concerns related to sales performance is ensuring sales people perform the sales process correctly. Unfortunately, most sales people have problems in the sales process, which causes their low performance. Islamic banks in Indonesia also experienced this situation, so a strategy needs to overcome this problem. For instance, using surveillance tools such as Sales Force Automation (SFA) with sales funnel theory. An SFA tool is a sales system connected to computers and internet networks. It monitors sales processes and results, manages contacts, forecasts sales, and analyzes sales performance daily and monthly. Additionally, it helps sales forces to measure the ability to achieve targets, plan sales strategies and customer approaches, and increase work motivation. Also, raise awareness of developing skills, and provide up-to-date information to supervisors about sales force performance to determine the proper training. Therefore, the use of SFA tools is expected to increase the productivity of sales people in optimizing the fulfillment of deposit targets in Islamic banking. This paper reports the SFA design in the form of a dashboard model with a visual sales to funnel that shows the function of the salesperson in conducting the sales process ends with the results. JEL Classification Codes: D40, E50, M31.